A physiological role for GABAB receptors and the effects of baclofen in the mammalian central nervous system - Misgeld, Ulrich; Bijak, Maria; Jarolimek, Wolfgang (Progress in neurobiology, 1995)
The inhibitory neurotransmitter GABA acts in the mammalian brain through two different receptor classes: GABAA and GABAB receptors. GABAB receptors differ fundamentally from GABAA receptors in that they require a G-protein. GABAB receptors are located pre- and/or post-synaptically, and are coupled to various K+ and Ca2+ channels presumably through both a membrane delimited pathways and a pathway involving second messengers. Baclofen, a selective GABAB receptor agonist, as well as GABA itself have pre- and post-synaptic effects. Pre-synaptic effects comprise the reduction of the release of excitatory and inhibitory transmitters. GABAergic receptors on GABAergic terminals may regulate GABA release, however, in most instances spontaneous inhibitory synaptic activity is not modulated by endogenous GABA. Post-synaptic GABAB receptor-mediated inhibition is likely to occur through a membrane delimited pathway activating K+ channels, while baclofen, in some neurons, may activate K+ channels through a second messenger pathway involving arachidonic acid. Some, but not all GABAB receptor-gated K+ channels have the typical properties of those G-protein-activated K+ channels which are also gated by other endogenous ligands of the brain. New, high affinity GABAB antagonists are now available, and some pharmacological evidence points to a receptor heterogeneity. The pharmacological distinction of receptor subtypes, however, has to await final support from a characterization of the molecular structure. The functional importance of post-synaptic GABAB receptors is highlighted by a segregation of GABAA and GABAB synapses in the mammalian brain.